Resilience: supporting children’s self-regulation in infant and toddler classrooms - Horm, Diane M.; Jeon, Shinyoung; Ruvalcaba, Denise Vega; Castle, Sherri (Frontiers in Psychology, 2024)
Introduction Resilience is a process that develops as a complex transaction as children experience and shape their social-ecological contexts. The dynamic development of self-regulation is an aspect of resilience that has received increased attention as a key mechanism predicting a variety of important short- and long-term outcomes. The current study examined how the self-regulation skills of infants and toddlers in a classroom could potentially shape classroom interactions and quality which, in turn, could potentially shape the development of self-regulation skills of the individual infants and toddlers enrolled in the classroom across an early childhood program year. The unique contribution of this study is the focus on a critical component of resilience, self-regulation, in an understudied age group, infants and toddlers, in an important and understudied context, the infant-toddler early childhood classroom. Methods Data are from a statewide evaluation of early childhood programs serving children birth to age 3 growing up in low-income contexts. Multi-level mediation models were employed to examine the mediation effect of classroom quality between classroom-level self-regulation and individual children’s gain in self-regulation over a year. Results We found a significant indirect path. The results showed that classroom-level self-regulation skills demonstrated by infants and toddlers in the fall predicted higher levels of teachers’ implementation of three important aspects of classroom quality – support for social-emotional, cognitive, and language development – in the winter. We also found that higher levels of teachers’ support for social-emotional, cognitive, and language development associated with children’s increased growth in self-regulation skills from fall to spring. The direct path from classroom-level self-regulation demonstrated in the fall to individual children’s gain in self-regulation was not significant. Discussion These findings, unique due to the focus on infants and toddlers in a classroom context, are discussed within the larger body of existing self-regulation research conducted with older children and prevalent theories outlining developmental mechanisms. Implications for both infant-toddler classroom practices and future research are addressed. Relative to practice, our findings have implications for informing how the development of self-regulation, an important component of resilience, can be supported in the youngest children, infants and toddlers, specifically those enrolled in center-based classrooms serving young children growing up in families with low incomes. We focus on the need to improve the support and professional development of infant-toddler teachers which, in turn, can improve classroom quality and foster resilience in infants and toddlers. Relative to research, our use of a relatively new measure of infant-toddler classroom quality, the Quality of Care for Infants and Toddlers (QCIT), shows how this tool can expand infant-toddler research, a need in the current literature. Future research using different measures, designs, analytical strategies, and diverse samples and contexts is needed to further explain very young children’s development of self-regulation, a critical component of resilience.